Symbolic exchange and death - Baudrillard, Jean, 1929-2007.; Sage eBooks (London : SAGE, 1993)
Aimed at students and academics in social and cultural theory, this book presents Baurillard's critical appraisal of social theories as diverse as traditional Marxism, cybernetics, ethnography, psychoanalysis, feminist thought, communications theory and semiotics.
Specialized.
Translated from the French.
Description based on print version record.
Keywords: Social psychology; Value; Death; Symbolism (Psychology); Electronic books